Pengolahan Sinyal Geomagnetik di Regional Lombok dengan Metode Fraktal - Bulkis Kanata; Teti Zubaidah; I Gusti Ayu Kusdiah (DIELEKTRIKA, 2020)
Lombok Island is one of the islands in Indonesia with a high level of seismic activity, because Indonesia itself is in the ring of fire. Mount Rinjani is an active volcano that can be associated with seismicity on the island which can affect changes in geomagnetic fields in this case can cause geomagnetic anomalies. Based on this, a study of the fractal dimensions of geomagnetic signals in the Lombok region used data of Kupang Observatory (KPG), Kakadu (KDU) and Guam (GUA) to determine anomalies that could be suspected as earthquake precursors. The fractal dimension of a destructive earthquake is seen in the range 12-43 days before the earthquake event and 5-46 days for small earthquakes. Fractal dimension values are linear with earthquake distance to the observatory.